A Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila Menggunakan Model Problem Based Learning (PBL) Berbantuan Media Powtoon di Kelas IV SD Negeri 03 Pakan Labuah Kota Bukittinggi: Pendekatan Problem Based Learning (PBL) dengan Media Powtoon dalam Meningkatkan Hasil Belajar Pendidikan Pancasila - Ferdinand, Yovella Patricya; Putera, Rafhi Febryan (Journal of Practice Learning and Educational Development, 2025)
This study was motivated by the low learning outcomes of students in learning Pancasila Education. Teachers are still unable to carry out the learning process using the Problem Based Learning (PBL) model assisted by Powtoon media properly and optimally. This results in student learning outcomes. This study aims to describe the use of the Problem Based Learning (PBL) model in the learning process to improve learning outcomes of Pancasila Education in elementary schools. This research is a class action research (PTK) conducted at SD Negeri 03 Pakan Labuah Bukittinggi City. The subjects of this study were class teachers and students totaling 20 students, consisting of 10 male students and 10 female students. The approaches used in this research are quantitative and qualitative approaches. The research was conducted in 2 cycles. Cycle I consisted of two meetings and cycle II consisted of one meeting. The research procedure consists of four stages, namely planning, implementation, observation, and reflection. The instruments used for data collection were observation sheets, test sheets, and non-tests. The results of this study are guided by the recapitulation table of the research results of Cycle I and Cycle II which have been presented in the discussion section. The results of this study showed an increase in: a) teaching module Cycle I with an average of 83.5% qualification (good) and increased in Cycle II to 94% with qualification (very good); b) implementation in the aspect of the teacher Cycle I with an average of 82% qualification (good) and increased in Cycle II to 96% with qualification (very good), in the aspect of students Cycle I with an average of 80% qualification (sufficient) and increased in Cycle II to 96% with qualification (very good); c) learning outcomes of students Cycle I with an average of 76.5 with qualification (sufficient) and increased in Cycle II to 91 with qualification (very good). Based on these results it can be concluded that using the Problem Based Learning (PBL) model assisted by Powtoon media can improve the learning outcomes of Pancasila Education in students.